2014
DOI: 10.1074/jbc.m114.580159
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of the Central Metabolite NAD Leads to Oncosis-mediated Cell Death

Abstract: Background: Depletion of NAD is a novel therapeutic strategy in oncology. Results: NAD depletion leads to loss of ATP and plasma membrane homeostasis. Conclusion: Although cells display evidence of apoptosis and autophagy, they predominantly die by oncosis caused by loss of ATP. Significance: We have identified a common pathway leading to cell death in response to NAD depletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 44 publications
7
56
0
Order By: Relevance
“…Because ATP levels are still maintained (∼75% of uninjured axons), delaying NAD + loss is sufficient to maintain ATP levels for a prolonged period, and thus extend axon health. Such findings are consistent with other reports suggesting that NAD + must be depleted below 5% to impact cell viability (29). These observations collectively demonstrate that SARM1 (K597E) impairs injury-induced activation of the SARM1 protein and reveal a surprising link between autoinhibition and N-terminal and SARM1 TIR domains.…”
Section: Mutant Sarm1 (K597e) Acts As a Dominant Negative And Blockssupporting
confidence: 81%
“…Because ATP levels are still maintained (∼75% of uninjured axons), delaying NAD + loss is sufficient to maintain ATP levels for a prolonged period, and thus extend axon health. Such findings are consistent with other reports suggesting that NAD + must be depleted below 5% to impact cell viability (29). These observations collectively demonstrate that SARM1 (K597E) impairs injury-induced activation of the SARM1 protein and reveal a surprising link between autoinhibition and N-terminal and SARM1 TIR domains.…”
Section: Mutant Sarm1 (K597e) Acts As a Dominant Negative And Blockssupporting
confidence: 81%
“…None of these events seem to be involved in BL plus APO866-induced cell death. Del Nagro and co-workers recently demonstrated that oncosis is the predominant form of cell death induced by NAMPT inhibitor, especially in treated-cancer cells that do not activate caspases [20] but this type of cell death was not addressed in the present study.…”
Section: Discussionmentioning
confidence: 64%
“…There is limited information on molecular mechanisms underlying the crosstalk between specific types of cancer cell death. A recent study (Del Nagro et al 2014) demonstrated that cancer cell lines with a slower rate of ATP depletion (average t 1 ⁄ 2 of 45 h) activate caspase-3 and show evidence of apoptosis and autophagy, whereas cell lines with rapid depletion of ATP (average t 1 ⁄ 2 of 32 h) do not activate caspase-3 or show signs of apoptosis or autophagy. Oncosis was identified as a predominant form of cell death once the ATP level was depleted by O20-fold.…”
Section: Discussionmentioning
confidence: 99%